Description of Eimeria motelo sp. n. (Apicomplexa: Eimeriidae) from the yellow footed tortoise, Geochelone denticulata (Chelonia: Testudinidae), and replacement of Eimeria carinii Lainson, Costa & Shaw, 1990 by Eimeria lainsoni nom. nov - Hůrková, L; Modrý, D; Koudela, B; Slapeta, J (Memorias do Instituto Oswaldo Cruz, 2000)
Eimeria motelo sp. n. is described from faeces of the yellow-footed tortoise, Geochelone denticulata (L.). Oocysts are irregularly ellipsoidal or cylindrical, with slightly expressed lobed protrusions and irregularities at the poles, possibly caused by wrinkling of the oocyst wall, 17 (15-19) x 9.4 (8.5-11) microm, shape index (length/width) being 1.81 (1.45-2). The oocyst wall is smooth, single-layered, 0.5 microm thick with no micropyle. There are no polar bodies. Sporocysts are ellipsoidal, 8.9 (7.5-10) x 4.4 (4-5) microm, shape index 2.03 (1.7-2.5). A sporocyst residuum is present, composed of many granules of irregular size. The sporozoites are elongate, lying lengthwise in the sporocysts. Comparison with other species of the genus Eimeria parasitising members of family Testudinidae indicates that the presently described coccidium represents a new species. The name of Eimeria carinii Lainson, Costa & Shaw, 1990 is found to be preoccupied by a homonym, Eimeria carinii Pinto 1928 given to a coccidium from Rattus norvegicus. Therefore, it is replaced by Eimeria lainsoni nom. nov.
Keywords: krysa rodu Rattus; Animals; želvy; Eimeria; Turtles; zvířata; Rats